THE ROLE OF THE UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) IN DEALING WITH THE VENEZUELAN REFUGEE CRISIS IN COLOMBIA IN 2018-2022 - Nita Oktavia (UNIDA GONTOR, 2021)
The study examined how the UNHCR was involved in addressing theVenezuelan refugee crisis in Colombia in 2018-2022 emerged as a result of theeconomic crisis in Venezuela. UNHCR as a special organization dealing with therefugee problem, played a significant role in helping the Colombian governmentdeal with the vast number of Venezuelan refugees coming to its country. The studyapplies a qualitative approach with a descriptive analysis technique that comesfrom primary and secondary data. This study has shown that as an international2organization, the UNHCR has the role of an initiation, a facilitator, a facilitator,a determinator, and a mediator. Whereas UNHCR’s humanitarian intervention isdone through its role as a facilitator. As a initiator, the UNHCR initiates theformation of a regional refugee and migrants response plan for Venezuela(RMRP). As a facilitator, the UNHCR along with other organizations focuses onhumanitarian intervention through the distribution of the 7 areas of facilities:education, food safety and nutrition, health, shelter. Integration, protection, andwash. As a determinator, the UNHCR supports Colombia with refugee statusrefugees (RSD). As the mediator, the UNHCR seeks a common solution to thewelfare of Venezuelan refugees through a GIFMM.